Valorization of Persimmon Fruit Through the Development of New Food Products - Hosseininejad, Sepideh; González, Cristina M.; Hernando, Isabel; Moraga, Gemma (Frontiers in Food Science and Technology, 2022)
Persimmon (Diospyros kaki Thunb.) fruits are among the most widely cultivated fruit crops worldwide, they are widespread in Asian countries and Europe, and their production is increasing along with the demand of consumers. Persimmon is a good source of nutrients and bioactive compounds, especially dietary fiber, carotenoids, and phenolic compounds, among other bioactive phytochemicals. However, persimmon is among the fruits, with a significant postharvest loss over the last few years. The cultivation of persimmon has a limited shelf life; it is a seasonal fruit and is perishable and difficult to store and transport; therefore, many persimmons are discarded. Currently, there is an increase in the valorization of the discarded persimmon fruits to generate opportunities and create a more sustainable system, in line with a possible circular economy. Therefore, in this review, we aim to compile an updated and brief revision of persimmons’ main chemical and bioactive compounds and the potential use of persimmon surpluses and by-products in developing new food products.